A Sensor Network Architecture for Tsunami Detection and Response. (2008) - Casey Casey, Kenan Kenan; Lim Lim, Alvin Alvin; Dozier Dozier, Gerry Gerry
Abstract : In this paper, we propose a sense and response system for tsunami detection and mitigation. We use the directed diffusion routing protocol as a baseline network protocol and develop several communication mechanisms to improve its performance. These include an efficient flooding technique, a route repair algorithm, and distributed services framework. We summarize the analysis mechanism used to predict tsunami propagation and briefly discuss the results of this algorithm. Finally, we describe potential barrier mechanisms and the real-time communication protocol that supports time-critical response of the system.